2021
DOI: 10.3390/molecules26020426
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis, Characterization and Modeling of CPO-27-Mg Metal-Organic Framework for Drug Delivery

Abstract: The coordination polymer CPO-27-Mg was rapidly synthesized under microwave irradiation. This material exhibits a sufficiently high drug loading towards aspirin (~8% wt.) and paracetamol (~14% wt.). The binding of these two molecules with the inner surface of the metal-organic framework was studied employing the Gaussian and Plane Wave approach of the Density Functional Theory. The structure of CPO-27-Mg persists after the adsorption of aspirin or paracetamol and their desorption energies, being quite high, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The results demonstrated that CPO-27-Mg could adsorb aspirin and paracetamol with high drug loading in vitro . 116 In another study, Xue et al used microwave-assisted synthesis to fabricate MIL-100, and used it to load DOX to treat breast cancer. 117 Studies focusing on using microwave-synthesized MOFs for stimulus-responsive drug delivery are still fewer.…”
Section: The Synthesis Of Mofs Used In Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…The results demonstrated that CPO-27-Mg could adsorb aspirin and paracetamol with high drug loading in vitro . 116 In another study, Xue et al used microwave-assisted synthesis to fabricate MIL-100, and used it to load DOX to treat breast cancer. 117 Studies focusing on using microwave-synthesized MOFs for stimulus-responsive drug delivery are still fewer.…”
Section: The Synthesis Of Mofs Used In Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…Their three-dimensional networks are composed of metal ions or small metal-oxide clusters as inorganic nodes connected through coordination bonds with polydentate organic molecule-linkers. MOF matrices show a number of outstanding properties, such as high crystallinity degree, large specific surface area and pore volume, and open pore structure, which is accessible for guest molecules as well as a possibility of the rational design of the framework due to the judicious choice of the inorganic nodes and organic linkers or their post-synthesis modification [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. These physicochemical characteristics make MOFs promising materials for versatile applications in adsorption, separation, and catalysis [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%